1988
DOI: 10.1007/bf00333413
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of pss genes of Rhizobium leguminosarum required for exopolysaccharide synthesis and nodulation of peas: Their primary structure and their interaction with psi and other nodulation genes

Abstract: Strains of Rhizobium leguminosarum (R.l.) biovar viciae containing pss mutations fail to make the acidic exopolysaccharides (EPS) and are unable to nodulate peas. It was found that they also failed to nodulate Vicia hirsuta, another host of this biovar. When peas were co-inoculated with pss mutant derivatives of a strain of R.l. by viciae containing a sym plasmid plus a cured strain lacking a sym plasmid (and which is thus Nod-, but for different reasons) but which makes the acidic EPS, normal numbers of nodul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 37 publications
0
62
1
Order By: Relevance
“…However, plants that form determinate nodules do not have such a requirement (16,31,54,64,67,68,81,88,94,95,121,134,175). The roles of rhizobial exopolysaccharides in symbiotic nodulation have been most thoroughly studied in S. meliloti.…”
Section: Bacterial Contributions To Infection Threadsmentioning
confidence: 99%
“…However, plants that form determinate nodules do not have such a requirement (16,31,54,64,67,68,81,88,94,95,121,134,175). The roles of rhizobial exopolysaccharides in symbiotic nodulation have been most thoroughly studied in S. meliloti.…”
Section: Bacterial Contributions To Infection Threadsmentioning
confidence: 99%
“…(1-31) [6], the Aspergillus nidulans qutG gene (QutG) [7] and the E.schrrichiu co/i suhB (SuhB) [4] and nmtA [S] genes (AmtA), and to the C-terminal peptide fragment inferred from the 3'end of an ORF upstream from the Rhizobium kguminowrutn pss gene [8] yielded homology scores of 27, 35, 43, 21 and IO s.d. units, respectively.…”
Section: Mai)p------woecmdyav1'lagqagevvrealk--------------nemmentioning
confidence: 99%
“…Homologies between IMP and the products of the Neurospora crassa qa-x [6] and Aspergillus nidulans qutG [7] genes, which are both part of a cluster of genes involved in quinic acid utilization, have been reported previously [l]. A search of the GenBank database (release 67) using the FASTA program [3] uncovered a fifth homology to an open reading frame (ORF) upstream from the pss gene of Rhizobium leguminosarum [8] which is required for exopolysaccharide (EPS) synthesis and nodulation of peas. (Only the 3' end of the sequence is known since the 5' end of this ORF was deleted during cloning of the fragment.…”
mentioning
confidence: 94%
“…Whatever the reason, this deficiency, unless overcome, will hamper future genetic analysis in this system. Sequence analysis initially indicated that at least some ex0 genes encoded proteins that were located in the bacterial membrane, since some had extremely hydrophobic regions (Borthakur et al, 1988;Gray & Rolfe, 1990). This was confirmed by the use ofphoA fusions into exo genes, several of which expressed alkaline phosphatase activity in R. meliloti and R. leguminosarurn (Long et al, 1988a;Latchford et al, 1991).…”
Section: Discussionmentioning
confidence: 99%